Depression and adherence to antiretroviral treatment in HIV-positive men in São Paulo, the largest city in South America: Social and psychological implications - de Moraes, Ricardo Pereira; Casseb, Jorge (Clinics (São Paulo, Brazil), 2017)
The aim of the present study was to investigate the prevalence of depression and adherence to antiretroviral treatment in two groups of individuals: men who have sex with men (MSM) and men who have sex with women (MSW). Two hundred and sixteen participants (MSM=116; MSW=100) who visited the Clinics Hospital of the School of the Medicine of the University of São Paulo completed two independent surveys (the BECK Depression Inventory and an adherence self-declared questionnaire) to evaluate their depression status and adherence to antiretroviral treatment, respectively. The study highlighted a positive relationship between depression and low adherence to Highly Active Antiretroviral Therapy in these patients regardless of age and sexual orientation. In addition, MSM subjects were two times more prone than MSW subjects to develop depression symptoms. White or mixed race men showed 7.6 times greater adherence to treatment than black men. The probability of complete adherence to treatment was 3.8 times higher in non-depressed subjects than in depressed subjects regardless of their ethnicity. The chance of developing depression was 4.17 times higher for an individual with non-adherent behavior than for an adherent individual. Individuals with low adherence rates have proportionally higher depression rates. Depressed men tend to show less adherence to treatment. Black but not mixed race or white men show less adherence to Highly Active Antiretroviral Therapy and have a greater chance of developing depression, which directly interferes with adherence. The chances of developing depression are four times greater for a patient with non-adherent behavior than for a patient with adherent behavior.